Quality of wood and pulp from a clone of Eucalyptus grandis planted at three locations - Sansígolo, Cláudio Angeli [UNESP]; Ramos, Éder Da Silva (Universidade Federal de Lavras (UFLA), 2011)
Eucalyptus grandis is one of the most popular species to use as raw material for pulp production in Brazil, as it provides excellent pulping, bleaching and papermaking results. The main objective of this study is to examine the quality of wood and pulp from a clone of Eucalyptus grandis, at age 4 years approximately, planted in three different soils, two of which being low fertility and one being a superior fertility soil, and their reflections on wood quality and pulping results. Chemical analyses of the soils followed guidelines developed by Raij et al. (2001), while physical and chemical properties of the wood followed ABTCP, TAPPI and ABNT standards. Chemical analyses of the soils pointed to lower fertility in Fazenda Limeira and Fazenda Tapera Queimada as opposed to higher fertility in Fazenda Mendes União. Results revealed stronger tendencies for the stand grown in the less fertile soils (Fazenda Limeira and Fazenda Tapera Queimada) in comparison to the stand grown in more fertile soil (Fazenda Mendes União) as to: higher wood and bark basic density, lower height and dry matter content, higher bark content, lower extractives content and higher holocellulose content, higher total and screened yields from pulping, lower specific wood consumption/t of pulp, and higher tear and tensile indices at low refining levels.

O Eucalyptus grandis é uma das espécies que mais se destacam como matéria prima para produção de polpa no Brasil, pois oferece excelentes resultados da polpação, branqueamento e fabricação de papel. Objetivou-se, com o presente trabalho, estudar a qualidade da madeira e da celulose de um clone de Eucalyptus grandis, com aproximadamente 4 anos, plantado em três solos diferentes, sendo dois solos de baixa fertilidade e um solo de fertilidade superior, e seus reflexos na qualidade da madeira e resultados da polpação. As análises químicas dos solos foram realizadas segundo as normas preconizadas por Raij et al. (2001) e as caracterizações físicas e químicas da madeira foram realizadas de acordo com as normas da ABTCP, TAPPI e ABNT. As análises químicas dos solos mostraram menores fertilidades para as Fazendas Limeira e Tapera Queimada e maior fertilidade para a Fazenda Mendes União. Os resultados mostraram fortes tendências para as árvores do clone plantadas nos solos de menor fertilidade (Fazendas Limeira e Tapera Queimada) em relação às árvores do clone plantadas no solo de melhor fertilidade (Fazenda Mendes União): maior densidade básica da madeira e casca; menores altura e teor de massa seca da árvore; maior teor de casca na árvore; menor teor de extrativos totais e maior teor de holocelulose; maior rendimento bruto e depurado da polpação; menor consumo específico de madeira/t de polpa e maiores índices de rasgo e tração em baixos níveis de refino.
Qualidade da madeira e da celulose de um clone de Eucalyptus grandis plantado em três locais
Keywords: Fertilidade do solo; propriedades da madeira; polpa Kraft; Soil fertility; wood properties; Kraft pulp